2021
DOI: 10.26226/morressier.613b545d842293c031b5b990
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visualization of Object-Oriented Variability Implementations as Cities

Abstract: Many large software systems are variability-rich, object-oriented, and implemented in a single code base. They then rely on multiple traditional techniques (inheritance, patterns) to realize variability, making these implementations not explicit. This directly hampers the comprehension of variability implementations, especially for newcomers in a project that need, in a short time, to understand the most important parts. In this paper, we propose VariCity, a visualization using the city metaphor to exhibit zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 51 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…While a feature model could be generated from the symfinder output, we believe it would not be as useful as a visualization related to the codebase itself. However, some additional work has demonstrated that the detected variability can be mapped to a domain feature model with an average precision 1 and a good recall [24,25]. The graph representation was also extended so that the mapped feature can be read while hovering on the different nodes representing the implementation classes.…”
Section: Metrics To Identify Oo Variability Implementationsmentioning
confidence: 99%
See 1 more Smart Citation
“…While a feature model could be generated from the symfinder output, we believe it would not be as useful as a visualization related to the codebase itself. However, some additional work has demonstrated that the detected variability can be mapped to a domain feature model with an average precision 1 and a good recall [24,25]. The graph representation was also extended so that the mapped feature can be read while hovering on the different nodes representing the implementation classes.…”
Section: Metrics To Identify Oo Variability Implementationsmentioning
confidence: 99%
“…The identification of such implementations can then be exploited in different ways, from the maintenance of the variable system to some variability reengineering [22] or a migration to a full software product lines [23]. For example, the result of the underlying detection used in our solution (i.e., symfinder ) has been successfully mapped to a domain feature model in two different variable systems [24,25]. However, we only focus in this article on a visualization adapted to the identification of the OO implemented variabilities to facilitate variability comprehension of large OO systems.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, CodeCity [17] and Evo-Streets [11] rely on the city metaphor to represent quality metrics on classes of an OO system. VariCity adapts the city metaphor to exhibit density of variability implementations [6] (cf. fig.…”
Section: A City-based Visualization 31 Varicitymentioning
confidence: 99%
“…The visualization provided by VariCity shows multiple improvements compared to the graph visualization of symfinder-2. Using a navigable 3D representation of a city where the buildings exhibit the different variability metrics and are grouped by usage allows to better grasp the organization of the classes [6]. Inheritance and additional usage relationships are displayed on hover not to overload the visualization.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation